Molybdenum-induced changes in the epiphyseal growth plate - Parry, N M; Phillippo, M; Reid, M D; McGaw, B A; Flint, D J; Loveridge, N (Calcified tissue international, 1993)
Molybdenum (Mo), at high concentrations, induces changes in the epiphyseal growth plate through its effects on copper (Cu) metabolism but it is unclear whether or not Mo can induce changes independent of its effects on copper status. To this end, the effect of Mo on longitudinal bone growth was examined in rats. Dietary Mo was given either as ammonium heptamolybdate or as ammonium tetrathiomolybdate, the latter producing a marked Cu deficiency. There was a significant reduction in longitudinal bone growth in both groups; however, growth plate width was increased only in the Cu-deficient animals due to an increase in the width of the zone of transitional/hypertrophic chondrocytes. Both glucose 6-phosphate dehydrogenase activity and cell proliferation (assessed by bromodeoxyuridine incorporation) were markedly decreased in the proliferating zone of the growth plate in both Mo-treated groups. These changes were not apparently related to changes in circulating vitamin D metabolites or insulin-like growth factor-1. The results indicate that excess Mo impairs cell proliferation within the growth plate, whereas the effects of copper deficiency are more related to chondrocyte differentiation. Thus, Mo can induce changes in longitudinal bone growth which are distinct from those resulting from Cu deficiency.